Characteristics and quality of clinical practice guidelines addressing acupuncture interventions: a systematic survey of 133 guidelines and 433 acupuncture recommendations. Issue 2 (24th February 2022) - Tang, Xiaorong; Shi, Xiaoshuang; Zhao, Hong; Lu, Liming; Chen, Ze; Feng, Yixuan; Liu, Lanping; Duan, Ruihua; Zhang, Pingping; Xu, Yuqin; Cui, Shuo; Gong, Fen; et al.
Abstract : Objective: To systematically summarise acupuncture-related Clinical Practice Guidelines (CPGs)'s clinical and methodological characteristics and critically appraise their methodology quality. Design: We summarised the characteristics of the guidelines and recommendations and evaluated their methodological quality using the Appraisal of Guidelines Research and Evaluation II (AGREE II) instrument. Data sources: Nine databases were searched from 1 January 2010 to 20 September 2020. Eligibility criteria for selecting studies: We included the latest version of acupuncture CPGs, which must have used at least one systematic review addressing the benefits and harms of alternative care options to inform acupuncture recommendations. Data extraction and synthesis: Reviewers, working in pairs, independently screened and extracted data. When there are statistical differences among types of CPGs, we reported the data by type in the text, but when not, we reported the overall data. Results: Of the 133 eligible guidelines, musculoskeletal and connective tissue diseases proved the most commonly addressed therapeutic areas. According to the AGREE II instrument, the CPG was moderate quality in the domain of clarity of scope and purpose, clarity of presentation, the rigour of development, stakeholder involvement and low quality in editorial independence, and applicability. The study identified 433 acupuncture-related recommendations; 380 recommended the use of acupuncture, 28 recommended against the use of acupuncture and 25 considered acupuncture but did not make recommendations. Of the 303 recommendations that used Grading of Recommendations Assessment, Development and Evaluation to determine the strength of recommendations, 152 were weak recommendations, 131 were strong recommendations, of which 104 were supported by low or very low certainty evidence (discordant recommendations). Conclusion: In the past 10 years, a large number of CPGs addressing acupuncture interventions exist. Although these guidelines may be as or more rigorous than many others, considerable room for improvement remains.